10.3: Invited Paper: High Mobility Oxide TFTs for Future LCD Applications. Issue 1 (1st July 2013) - Song, Junho; Lim, Jun Hyung; Du Ahn, Byung; Lee, Jehun
Abstract: In this study, we reported the capability of a new composition oxide TFTs, fabricated using sputtering process and successfully developed including sputtering target with single‐phase. In order to compare single‐phase target with multiphase target, as‐deposited films by same sputtering condition for sputtering process were prepared and the chemical characterization of target, as‐deposited film, and annealed films, respectively by using EPMA and ICP analyses were evaluated. Single‐phase target had a uniform and homogeneous metal composition distribution without segregation. In addition, after annealing process, the films were maintained the chemical composition. We, therefore, selected single target and evaluated the electrical performances. The saturation mobility (μsat ) was measured to be 22.4 cm 2 V −1 s −1 . In addition, threshold voltage (Vth ) was 0.75 V and subthreshold swing (SS) was 0.44 V/decade, respectively. This study could encourage in developing a novel composition oxide TFTs with high mobility.